Bioresource collection of biosamples from pregnant women at different gestational ages for the search for early biomarkers of pregnancy complications and potential for its use in research - O. V. Pachulia; R. A. Illarionov; E. S. Vashukova; A. R. Maltseva; T. B. Postnikova; Yu. A. Nasykhova; O. N. Bespalova; A. S. Glotov (Кардиоваскулярная терапия и профилактика, 2022)
Aim. Clinical and anamnestic characterization of the bioresource collection of biosamples from pregnant women at different gestational ages.Material and methods. Preparation of biosamples of various biomaterial types for long-term storage; static analysis of clinical and anamnestic characteristics of women whose samples are included in the collection.Results. As of September 1, 2022, the collection consists of 16625 biosamples of various biomaterial types from 355 pregnant women. The clinical and anamnestic characteristics of women, samples of which are presented in the collection, are presented.Conclusion. The resulting high-quality biosamples can be used in various basic and applied research to study both the physiological and pathological course of pregnancy. Particularly promising is the possibility of searching for the earliest biomarkers of gestational complications before the onset of obstetric complications. In this regard, it is important to have complete clinical and anamnestic data on biosamples of the collection in order to expand the possibilities of its use and improve the quality of ongoing research.